The PK/PD Interactions of Doxycycline against Mycoplasma gallisepticum - Zhang, Nan; Gu, Xiaoyan; Ye, Xiaomei; Wu, Xun; Zhang, Bingxu; Zhang, Longfei; Shen, Xiangguang; Jiang, Hongxia; Ding, Huanzhong (Frontiers in Microbiology, 2016)
Mycoplasma gallisepticum (MG) is one of the most important pathogens that cause chronic respiratory disease (CRD) in chicken. This study investigated the antibacterial activity of doxycycline against Mycoplasma gallisepticum strain S6. In static time-killing studies with constant antibiotic concentrations (0 to 64MIC), MG colonies were quantified and kill rates were calculated to estimate the drug effect. The half-life of doxcycycline in chicken was 6.51±0.63 h. An in vitro dynamic model (the drug concentrations are fluctuant) was also established and two half-lives of 6.51 h and 12 h were simulated. The samples were collected for drug concentration determination and viable counting of MG. In static time-killing studies, doxycycline produced a maximum antimycoplasmal effect of 5.62 log10 (CFU/mL) reduction and the maximum kill rate was 0.11 h-1. In the in vitro dynamic model, doxycycline had a mycoplasmacidal activity in the two regimens, and the maximum antimycoplasmal effects were 4.1 and 4.75 log10 (CFU/mL) reduction, respectively. Furthermore, the cumulative percentage of time over a 48 h period that the drug concentration exceeds the MIC (%T>MIC) was the pharmacokinetic-pharmacodynamic (PK-PD) index that best correlated with antimicrobial efficacy (R2 =0.986, compared with 0.897 for the peak level divided by the MIC and 0.953 for the area under the concentration-time curve over 48h divided by the MIC). The estimated %T>MIC values for 0 log10 (CFU/mL) reduction, 2 log10 (CFU/mL) reduction and 3 log10 (CFU/mL) reduction were 32.48%, 45.68% and 54.36% respectively during 48 h treatment period of doxycycline. In conclusion, doxycycline shows excellent effectiveness and time-dependent characteristics against MG strain S6 in vitro. Additionally, these results will guide optimal dosing strategies of doxycycline in MG infection. Keywords: Mycoplasma gallisepticum, doxycycline, PK/PD, in vitro model, kill rate